Community structure of metazoan parasites of silverside, Odontesthes bonariensis (Pisces, Atherinopsidae) from Argentina - Drago, Fabiana Beatriz (2012)
The helminth communities of silverside, Odontesthes bonariensis (Valenciennes, 1835), from two Argentinean lagoons were studied and compared at component community and infracommunity levels. Nine helminth species were found: five digeneans (Austrodiplostomum cf. mordax, Ascocotyle (Phagicola) cf. diminuta, Ascocotyle sp., Thometrema bonariensis and Saccocoelioides sp.); two nematodes (Contracaecum sp. and Hysterothylacium sp.); one acanthocephalan (Wolffhugelia matercula) and one cestode (Cangatiella macdonaghi). Odontesthes bonariensis is a new host record for five parasite species. Richness, diversity and number of helminths in silversides from Salada Grande lagoon were higher than in those from Lacombe lagoon. This could be related with lagoon size, abundance of mollusks and fish-eating birds, and size and diet of silversides captured in each lagoon. In Salada Grande lagoon the helminth community of silversides was dominated by the allogenic and generalist species A. cf. mordax; while the autogenic and intermediate specialist species C. macdonaghi was dominant in Lacombe lagoon. Host sex did not affect richness, diversity or total abundance, whereas host size was positively correlated with these attributes, except diversity in Salada Grande lagoon.